1973
DOI: 10.2134/jeq1973.00472425000200020019x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ozone by Soil

Abstract: Simultaneous measurements of the vertical profiles of horizontal wind, temperature, and ozone concentration above a bare, freshly cultivated fine sandy loam were obtained on 12 occasions during a 4-day period in July when ozone concentrations ranged from 8 to 26 X 10 z molecules (mol) -3 (1X 101~ tool cm =3 ---4 ppb = 8/~g m-3). The decrease in ozone near the soil surface clearly indicated that the soil was removing ozone from the atmosphere. The rate of ozone removal varied from 3 to 12 )< 10~z mol cm -2 sec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1975
1975
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…For example, Aldaz (1969) recommends a value of deposition velocity (vertical flux divided by concentration at a specified height) of 0.02 cm s-l over snow and 0.04 cm s-l over water. These estimates are about an order of magnitude smaller than values found above vegetation in the daytime and over bare soil not saturated with water (Regener, 1957;Regener and Aldaz, 1969;Aldaz, 1969;Galbally, 1971;Turner et al, 1973;Wesely et al, 1978;Garland and Derwent, 1979;Leuning et al, 1979). Galbally and Allison (1972) report fluxes over snow equivalent to deposition velocities that range from 1.7 to -3.3 cm s-l , depending on the condition of the snow surface.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, Aldaz (1969) recommends a value of deposition velocity (vertical flux divided by concentration at a specified height) of 0.02 cm s-l over snow and 0.04 cm s-l over water. These estimates are about an order of magnitude smaller than values found above vegetation in the daytime and over bare soil not saturated with water (Regener, 1957;Regener and Aldaz, 1969;Aldaz, 1969;Galbally, 1971;Turner et al, 1973;Wesely et al, 1978;Garland and Derwent, 1979;Leuning et al, 1979). Galbally and Allison (1972) report fluxes over snow equivalent to deposition velocities that range from 1.7 to -3.3 cm s-l , depending on the condition of the snow surface.…”
Section: Introductionmentioning
confidence: 75%
“…Hence, snow appears to have a characteristic surface resistance of about 34 s cm-', whether thawing or not, but might be less for very fresh snow. , about one third that for snow, but a factor of 10 greater than that likely for much drier soil (Turner et al, 1973).…”
Section: Snowmentioning
confidence: 84%
See 1 more Smart Citation
“…There is evidence though that 0 3 is removed by the oceans to some extent (Aldaz, 1969). Ozone is also absorbed by vegetation (Hill, 1971;Hill and Littlefield, 1969;Rich et al, 1970), and soil (Junge, 1962;Kroening and Ney, 1962;Aldaz, 1969;Turner et al, 1973). Aldaz (1969) has shown that soil and vegetation probably represent a major sink for this gas.…”
Section: Removal Mechanismsmentioning
confidence: 99%
“…Ozone does not penetrate the soil surface 18 and consequently, must influence mycorrhizae by altering plant metabolism. The soluble carbohydrates of roots are generally considered a major factor in mycorrhizal infection 19 and, thus, any effect of O3 on the availability of root sugars would be of importance to the carbohydrate metabolism of the associated fungi.…”
mentioning
confidence: 99%